Role of Ionizing Radiation Techniques in Polymeric Hydrogel Synthesis for Tissue Engineering Applications - Ion Călina; Maria Demeter; Anca Scărișoreanu; Awn Abbas; Muhammad Asim Raza (Gels)
Hydrogels are widely utilized in industrial and scientific applications owing to their ability to immobilize active molecules, cells, and nanoparticles. This capability has led to their growing use in various biomedical fields, including cell culture and transplantation, drug delivery, and tissue engineering. Among the available synthesis techniques, ionizing-radiation-induced fabrication stands out as an environmentally friendly method for hydrogel preparation. In alignment with the current requirements for cleaner technologies, developing hydrogels using gamma and electron beam irradiation technologies represents a promising and innovative approach for their biomedical applications. A key advantage of these methods is their ability to synthesize homogeneous three-dimensional networks in a single step, without the need for chemical initiators or catalysts. Additionally, the fabrication process is controllable by adjusting the radiation dose and dose rate.